2021
DOI: 10.1080/09502386.2021.1898019
|View full text |Cite
|
Sign up to set email alerts
|

Following the science? Covid-19, ‘race’ and the politics of knowing

Abstract: The UK government has consistently claimed to be 'following the science' in its approach to the pandemic but this claim conceals complex and shifting entanglements of politics and science. The instability of the relationship between politics and science became increasingly visible around the unequal vulnerability of racialized minorities to infection and death from Covid-19. How and when Black and other minoritized deaths matter has become the focus of UK governmental efforts to delay and deflect, in what has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Yet those campaigning to protect the NHS through evoking national spatial imaginaries must be continuously alert to how the very idea of ‘universal’ healthcare is susceptible to co-option in the name of nationalism and racial exclusion. And not only has the global pandemic stressed the ongoing importance of nations and states within policymaking, but governmental strategies of depoliticisation and deferral through ‘following the science’ raise fundamental questions over whose lives are deemed to matter (Clarke, 2021). Rethinking the times and spaces of politics and policy, there is a need for policy mobilities scholarship to grapple with shifting articulations of nation, state and welfare in the current conjuncture.…”
Section: Discussionmentioning
confidence: 99%
“…Yet those campaigning to protect the NHS through evoking national spatial imaginaries must be continuously alert to how the very idea of ‘universal’ healthcare is susceptible to co-option in the name of nationalism and racial exclusion. And not only has the global pandemic stressed the ongoing importance of nations and states within policymaking, but governmental strategies of depoliticisation and deferral through ‘following the science’ raise fundamental questions over whose lives are deemed to matter (Clarke, 2021). Rethinking the times and spaces of politics and policy, there is a need for policy mobilities scholarship to grapple with shifting articulations of nation, state and welfare in the current conjuncture.…”
Section: Discussionmentioning
confidence: 99%
“…Existing writing on the place of the face mask in the pandemic, from the cultural studies perspective, has fruitfully revealed the ways in which masks and debates about government directives to wear them have been embedded into right-wing performative politics, including toxic masculinity (Harsin, 2020) and white supremacy (Clarke, 2021; Silva, 2021; Smicker, 2021). Although the face mask has become a new site for culture wars and highly visible forms of ‘toxic mask-ulinity’ (Palmer and Peterson, 2020), the science is clear on the important role that face masks play in preventing or minimising virus spread.…”
Section: Face Masks: Political Flashpoint or Scientific Intervention?mentioning
confidence: 99%
“…The widely reported and discussed differences in Covid-19 mortality rates between privileged and underprivileged racial and ethnic groups, from Black and white Americans, to populations of the Global North and South, opened up to view the social, economic, political and overall life inequities through which biopower operates. At these times of crisis, the lives of certain populations became equal to ‘racial contagion’ (as in the case of Asian Americans, see Mallapragada, 2021 ), and the lives of racialized minorities disproportionately lost in Western metropoles – stark reminders of deep and long-standing structural racism (Clarke, 2021 ).…”
Section: Introduction To the Special Issue On Covid-19 As A Global Cr...mentioning
confidence: 99%